Circumstances, Which are to be Established in Road Traffic Crime Cases - Aksenova, Laila Y. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
On the basis of the subject of proof (Art. 73 Code of Criminal Proceedings), clarification of higher courts in Russia, certain regulatory sources, author formulated range of circumstances to be established in cases of road traffic offenses, necessary in particular for the decision to initiate criminal proceedings in cases of road traffic offenses.